2021
DOI: 10.3390/ijerph18094521
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Corporate Social Responsibility at Employee Level, Ethical Leadership, Quality of Work Life and Employee Pro-Environmental Behavior: The Case of Healthcare Organizations

Abstract: The notion of corporate social responsibility (CSR) has been around for many decades. However, even in 2021, its spectrum is still evolving. Several studies addressed CSR for realizing different organizational outcomes. However, its significance in achieving employee-related consequences is relatively new to the literature. In the same manner, it is not clear from existing literature how ethical leaders can impact their followers’ CSR-related behavior, for example, employee pro-environmental behavior (EPB). Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 109 publications
3
46
0
2
Order By: Relevance
“…In this regard, very few studies have attempted to investigate the mediating effect of a leadership style to shape the behavior of employees. To our knowledge, only the studies of Molnár et al [ 21 ] and Murtaza et al [ 27 ] have followed a similar approach. Nonetheless, many studies have highlighted the direct importance of a leadership style, especially an ethical style of leadership, to spur employees’ pro-environmental behavior [ 81 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, very few studies have attempted to investigate the mediating effect of a leadership style to shape the behavior of employees. To our knowledge, only the studies of Molnár et al [ 21 ] and Murtaza et al [ 27 ] have followed a similar approach. Nonetheless, many studies have highlighted the direct importance of a leadership style, especially an ethical style of leadership, to spur employees’ pro-environmental behavior [ 81 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, in healthcare settings, in different recent studies, it has been reported that there is a positive relationship between CSR and pro-environmental behavior. For example, the study of Molnár et al [ 21 ] stated that the CSR orientation of a hospital enterprise has a positive relationship with employees’ pro-environmental behavior. Similarly, the same positive relationship was reported in a recent study by Ahmad et al [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…CSR-specific initiatives are undertaken by an organization to earn a belief from all stakeholders that such moves will bring positive results for all stakeholders [2]. Employees are important stakeholders for the success of an organization [3]. Specifically, from the perspective of the banking sector, it has been reported that employees working for a socially responsible bank are more productive and engaged as compared to the employees of a bank that does not consider CSR as an important strategic enabler [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%